Development of intensity – duration – frequency curves using combined rain gauge and remote sense datasets for Weta Traditional Area in Ghana - Mawufemor Dzamposu Agakpe; Mexoese Nyatuame; Francis Ampiaw (HydroResearch, 2024)
This research developed IDF curves and derived empirical equations for the Weta Area to estimate design rainfall. Daily rainfall data of Rain Gauge and Tropical Rainfall Measuring Mission (TRMM) 3B42 over 22 years for Weta were obtained from the Ghana Meteorological Services and National Aeronautics and Space Administration, respectively. The Indian Meteorological Department formula was used to disaggregate the daily data into hourly synthetic series to develop the IDF curves. The combined dataset was subjected to frequency analysis to determine the distribution which best characterize the dataset. The results demonstrated that the IDF curves provided higher intensities for shorter durations (0.08 h, 0.17 h, 0.25 h, and 0.5 h) while lower intensities for longer durations (1 h, 2 h, 6 h, 12 h and 24 h). The rainfall intensities and return periods are parallel and high intensities correlated with brief durations for the same return period. TRMM overestimated rainfall compared to Rain Gauge data. The IDF curves and derived empirical equations are useful scientific tools for hydraulic infrastructure design and water resources planning and management.